2000
DOI: 10.1097/00001648-200005000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Low-Income African-American Mothers’ Perception of Exposure to Racial Discrimination and Infant Birth Weight

Abstract: We performed a hospital-based case-control study of African-American mothers to explore the relation between a mother's perception of exposure to racial discrimination during pregnancy and very low birth weight. We administered a structured questionnaire to low-income mothers of very low birth weight (<1500 gm; N = 25) and non-low birth weight (>2500 gm; N = 60) infants. The unadjusted and adjusted odds ratio of very low birth weight for maternal exposure to racial discrimination were 1.9 (0.5-6.6) and 3.2 (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 14 publications
3
116
2
1
Order By: Relevance
“…Our study complements the few existing empirical studies of racism and infant health outcomes. However, not unlike other studies that have investigated racism and birth outcomes, [28][29][30]48 our observed association between racism and low birth weight did not attain statistical significance in adjusted analyses, and therefore our empirical findings are only mildly suggestive of a relationship. We relied on retrospective selfreports of birth outcomes from a sample birth cohort that cannot be generalized to the counties, and our sample may have been inadequately powered for the measured associations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study complements the few existing empirical studies of racism and infant health outcomes. However, not unlike other studies that have investigated racism and birth outcomes, [28][29][30]48 our observed association between racism and low birth weight did not attain statistical significance in adjusted analyses, and therefore our empirical findings are only mildly suggestive of a relationship. We relied on retrospective selfreports of birth outcomes from a sample birth cohort that cannot be generalized to the counties, and our sample may have been inadequately powered for the measured associations.…”
Section: Discussioncontrasting
confidence: 99%
“…[21][22][23] Perceived discrimination has been associated with low selfrated mental and physical health, [24][25][26] low birth weight, [27][28][29] and preterm delivery 30,31 among African Americans. Perceived discrimination has also been associated with hypertension 32,33 and smoking, 34 which are risk factors during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Racism has a strong and lasting impact on the health of minorities [66][67][68][69][70] ; however, few respondents endorsed racism and discrimination as a significant childhood stressor. We expected the large percentage of racial/ethnic minorities participating in our study, having grown up in disadvantaged racially segregated communities, would list discrimination as one of the predominant stressors in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Collins et al investigated the causal mechanisms of this association. When other risk factors, such as socioeconomic condition, levels of support, cigarette smoking, alcohol and illicit drug use were excluded, they reported that African American mothers with very low birth weight infants, less than 1500g, were twice as likely to report experiences of racial discrimination during pregnancy than women who had infants of normal birth weight (more than 2500g) (Collins, et al, 2000). This elevated rate may account for the difference in the pre-term birth rate between the USA and other countries.…”
Section: Ethnicitymentioning
confidence: 99%